Andrographis echioides (Family: Acanthaceae): A New Addition to the Flora of Andaman and Nicobar Islands, India - Gosavi, K. V. C.; Mane, S. S. (Journal of the Bombay Natural History Society (JBNHS), 2018)
No Abstract.